A National Strategy to Diagnose Coronavirus Disease 2019–Associated Invasive Fungal Disease in the Intensive Care Unit. (29th August 2020) - White, P Lewis; Dhillon, Rishi; Cordey, Alan; Hughes, Harriet; Faggian, Federica; Soni, Shuchita; Pandey, Manish; Whitaker, Harriet; May, Alex; Morgan, Matt; Wise, Matthew P; Healy, Brendan; et al.
Abstract: Background: Fungal coinfection is a recognized complication of respiratory virus infections, increasing morbidity and mortality, but can be readily treated if diagnosed early. An increasing number of small studies describing aspergillosis in coronavirus disease 2019 (COVID-19) patients with severe respiratory distress are being reported, but comprehensive data are lacking. The aim of this study was to determine the incidence, risk factors, and impact of invasive fungal disease in adult COVID-19 patients with severe respiratory distress. Methods: An evaluation of a national, multicenter, prospective cohort evaluation of an enhanced testing strategy to diagnose invasive fungal disease in COVID-19 intensive care patients. Results were used to generate a mechanism to define aspergillosis in future COVID-19 patients. Results: One-hundred and thirty-five adults (median age: 57, M/F: 2.2/1) were screened. The incidence was 26.7% (14.1% aspergillosis, 12.6% yeast infections). The overall mortality rate was 38%; 53% and 31% in patients with and without fungal disease, respectively ( P = .0387). The mortality rate was reduced by the use of antifungal therapy (mortality: 38.5% in patients receiving therapy vs 90% in patients not receiving therapy ( P = .008). The use of corticosteroids ( P = .007) and history of chronic respiratory disease ( P = .05) increased the likelihood of aspergillosis. Conclusions: Fungal disease occurs frequently in critically ill, mechanically ventilated COVID-19 patients. The survival benefit observed in patients receiving antifungal therapy implies that the proposed diagnostic and defining criteria are appropriate. Screening using a strategic diagnostic approach and antifungal prophylaxis of patients with risk factors will likely enhance the management of COVID-19 patients. Abstract : Invasive fungal disease represents a significant complication associated with severe coronavirus disease 2019 infection, resulting in increased mortality. Using early antifungal therapy, directed by strategic mycological testing, infers a survival benefit. Antifungal prophylaxis may be warranted in certain patients.